My rows and piles of coins - Mollel, Tololwa M. (Tololwa Marti) (Clarion Books, 1999)
A Tanzanian boy saves his coins to buy a bicycle so that he can help his parents carry goods to market, but then he discovers that in spite of all he has saved, he still does not have enough money.